2020
DOI: 10.1017/s1368980019003586
|View full text |Cite
|
Sign up to set email alerts
|

What to expect from the price of healthy and unhealthy foods over time? The case from Brazil

Abstract: Objective:To measure change in price of food groups over time (1995–2030) in Brazil, considering the Brazilian Dietary Guidelines’ recommendations.Design:Data from the Household Budget Survey (2008–2009 HBS) and the National System of Consumer Price Indexes (NSCPI) were used to create a data set containing monthly prices for the foods and beverages most consumed in the country (n 102), from January 1995 to December 2017. Data on price of foods and beverages from 2008–2009 HBS (referring to January 2009) were u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
99
0
22

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 82 publications
(122 citation statements)
references
References 21 publications
1
99
0
22
Order By: Relevance
“…In addition, another fact that may contribute to the lower consumption of ultra-processed foods in this region is that the average price of in natura and minimally processed foods in Brazil (R$ 2.28/1000 kcal) is lower than the average price of ultra-processed foods (R$ 2.40/1000 kcal) [ 66 ]. However, a recent study identified that since the beginning of the 2000s the price of ultra-processed foods has undergone successive reductions in Brazil, becoming cheaper than processed foods, and it is predicted that unhealthy foods will become cheaper than healthy ones in 2026 [ 67 ]. As expected, the lowest caloric contribution of the farmers' diet provided by the group of processed food, as in Brazil (10.6%) [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, another fact that may contribute to the lower consumption of ultra-processed foods in this region is that the average price of in natura and minimally processed foods in Brazil (R$ 2.28/1000 kcal) is lower than the average price of ultra-processed foods (R$ 2.40/1000 kcal) [ 66 ]. However, a recent study identified that since the beginning of the 2000s the price of ultra-processed foods has undergone successive reductions in Brazil, becoming cheaper than processed foods, and it is predicted that unhealthy foods will become cheaper than healthy ones in 2026 [ 67 ]. As expected, the lowest caloric contribution of the farmers' diet provided by the group of processed food, as in Brazil (10.6%) [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although evidence suggests an economic advantage in meals prepared at home in comparison with its substitution for ultra-processed foods (due to the lowest price per calorie of the first one)highlighting bean and rice as an economic alternative for the adoption of a healthier food practice (28) a recently published study analysing data from 1995 to 2030 indicated that this scenario has been changing unfavourably to the consumption of healthy foods (29) . Even though no data on the perception of consumers on this price trend are available, this might constitute an important influence on the reduction of consumption observed among our results, since it impacts not only the own price of beans but also the price of complementary items (such as rice) and potentially substitutes (such as ready to eat ultra-processed items).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, there are several environmental factors that also influence consumers food choice such as price, availability and access to foods, the rapidity in the consumption of no-cook meals and the aggressive advertising and marketing of brands (3,32,40) . In a sense that, basic and traditional foods are being replaced by the convenience of ultra-processed food products (3,(15)(16)(17)29) . The main outcome of this shift in consumption is the reduction in food quality and the deterioration of healthy/traditional/habitual and cultural dietary patterns (25)(26)(27) .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, UPF did not increase in price as much as unprocessed and minimally processed foods over the last 12 years [20]. In Brazil, in 1995, UPF were the most expensive food group, but the price of UPF underwent successive reductions since the year 2000 and was forecasted to become cheaper than MPF by 2026 [21]. Results from the Brazilian Household Budget Survey 2008-2009, including a random sample of 55,970 households, found that mean prices of foods and beverages purchased at supermarkets were 37% lower in comparison to other food stores, and the share of UPF in purchases made at supermarkets was 25% higher than at other food stores [22].…”
Section: Introductionmentioning
confidence: 97%